Sustainable economic growth potential of biomass-enriched countries through bioenergy production: State-of-the-art assessment using product space model - Ayub, Aqsa; Ali Shah, Syed Fahad; Qyyum, Muhammad Abdul; Habib, Dur-e-Yab; Murtaza, Malik Ashir; Rehan, Mohammad; Tabatabaei, Meisam; Aghbashlo, Mortaza; Waqas, Muhammad; Nizami, Abdul-Sattar (Frontiers in Energy Research, 2023)
The current study aims to examine the economically viable biomass feedstocks for bioenergy generation and their export potential. The Product Space Model (PSM) was the primary tool used to achieve the aim by accomplishing certain objectives. The study's findings showed that Pakistan has abundant biomass resources for energy production. Canola oil, leather flesh wastes, and poultry fattening showed the highest PRODY values 46735, 44438, and 41791, respectively. These have high-income potential and considers feasible for export after meeting local energy demand. While goat manure, cashew nutshell, and cotton stalk have noticed lower income potential having values 3641, 4225, and 4421, respectively. The bio-wastes having low-income potential are more beneficial to utilize in energy generation plants within the country. USA was observed to make the most sophisticated products, indicated by EXPY value 36296.89. While the minimum level of sophistication was observed for Indonesia, as revealed by its EXPY value 22235.41 among all considered countries. The study has practical applications in economic, social, and environmental perspectives, focusing on economic, clean, and sufficient energy. Furthermore, it identified exportable biomass feedstocks to strengthen Pakistan's economy. Further research must be conducted to evaluate other indicators of the Product Space Model, as it would provide a clearer picture of bioenergy and biomass export prospects.